2000
DOI: 10.2169/internalmedicine.39.655
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Primary Adenocarcinoma of the Lung and Leiomyosarcoma of the Small Intestine.

Abstract: The occurrence of synchronous epithelial cancer of the lung and leiomyosarcoma of the small intestine is rare. We report here the case of a 62-year-old manwith adenocarcinoma of the lung in clinical stage IIIB (T4N0M0). After two courses of chemotherapy (cisplatin, 80 mg/m2 and mitomycin C, 8 mg/m2) the patient developed symptoms of a small bowel obstruction. Palliative surgical resection was performed and a leiomyosarcomaof the small intestine was found and defined by an immunohistological study. The resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In their review of 5505 sarcomas, Grobmyer et al [20] reported only for 2 patients (0.04%) who presented with synchronous soft tissue sarcomas of distinct pathology. This was also the case for sarcomas associated with other malignnant neoplasms, such as lymphoma [21,22] or adenocarcinoma [23,24]. Both Merimsky et al [25] and Geva et al [26] have respectively shown that 7.5% of soft tissue sarcoma patients developed other malignant neoplasms either before or after the initial sarcoma diagnosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In their review of 5505 sarcomas, Grobmyer et al [20] reported only for 2 patients (0.04%) who presented with synchronous soft tissue sarcomas of distinct pathology. This was also the case for sarcomas associated with other malignnant neoplasms, such as lymphoma [21,22] or adenocarcinoma [23,24]. Both Merimsky et al [25] and Geva et al [26] have respectively shown that 7.5% of soft tissue sarcoma patients developed other malignant neoplasms either before or after the initial sarcoma diagnosis.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Park et al [32] emphasized performing adequate pre-surgical evaluation and a comprehensive biopsy, even though a painless, movable soft tissue sarcoma of the extremity is likely a benign tumor. Takemoto et al [24] emphasized the necessity of using immunohistochemistry in the differential diagnosis of sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases are sporadic or are associated with a genetic syndrome (Peutz-Jeghers syndrome, NF1), Meckel's diverticulum, or other neoplasms (retroperitoneal sarcoma, lung carcinoid) (3).…”
mentioning
confidence: 99%